Raba predlogov in predložnih zvez pri slovensko govorečih predšolskih otrocih - Vidovič, Janja (Rehabilitacija (Ljubljana), 2023)
Background: There has been little research on the use of prepositions among Slovene-speaking children, despite the fact that preposition- learning tasks feature frequently in speech therapy. The goal of our research was to study the typical age at which children understand and acquire the prepositions in, on, under, in front of, behind, by and between, whether they understand prepositions prior to their use in speech, and whether the deictic usage of prepositions decreases with age. Methods: We acquired data on 88 Slovene-speaking children, aged from 2 years to 4years 11 months, who took part in the standardisation of the Slovene version of the New Reynell Development Scale. Based on their answers, we described the distribution of prepositions for each age group. Using statistical tests, we checked whether the results of comprehension exercises were better than the results of expression exercises, and whether the deictic usage of prepositions decreases with age. Results: The results showed that less than half of 2-year-olds use the prepositions in, on, under, next to and behind, while in front of and between do not occur. Among 3-year-olds, more than half of the children use the prepositions in, on, and under, while less than half of the children use in front of, next to, between. All the 4-year-old children used in, on, behind, and under, while. The results showed that children do significantly better in preposition comprehension exercises than they do in expression exercises. We also confirmed that the deictic use of prepositions decreases with age, especially from the age of 4 onwards. Conclusion: The study offers an insight into the use of prepositions among Slovene-speaking children. We found that they acquire prepositions at a rate comparable to the reports in the current literature, with minor disparities, and confirmed our hypotheses that the children understand prepositions before they learn to use them and that the deictic use of prepositions decreases with age.
Keywords: deictic use of prepositions; deiktičnost; logopedija; predšolski otrok; preschool child; prostorski predlogi; spatial prepositions; speech-language therapy